2014
DOI: 10.1128/jb.01716-14
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of the mamAB and mms6 Operons Reveals a Gene Set Essential for Magnetosome Biogenesis in Magnetospirillum gryphiswaldense

Abstract: c Biosynthesis of bacterial magnetosomes, which are intracellular membrane-enclosed, nanosized magnetic crystals, is controlled by a set of >30 specific genes. In Magnetospirillum gryphiswaldense, these are clustered mostly within a large conserved genomic magnetosome island (MAI) comprising the mms6, mamGFDC, mamAB, and mamXY operons. Here, we demonstrate that the five previously uncharacterized genes of the mms6 operon have crucial functions in the regulation of magnetosome biomineralization that partially o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
149
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(158 citation statements)
references
References 58 publications
6
149
0
3
Order By: Relevance
“…The results of biochemical analyses of gene mutants and proteins have indicated that the complex process of magnetosome biosynthesis is routed through multiple steps by using various magnetosome proteins (11-13, 15, 39). A number of proteins involved in the process are derived from invagination of the cytoplasmic membrane, whereas some may be assembled on the magnetosome surface or inserted into the membrane during magnetosome maturation (12,31). The complex magnetosome formation process is considered to require the spatial regulation of magnetosome proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of biochemical analyses of gene mutants and proteins have indicated that the complex process of magnetosome biosynthesis is routed through multiple steps by using various magnetosome proteins (11-13, 15, 39). A number of proteins involved in the process are derived from invagination of the cytoplasmic membrane, whereas some may be assembled on the magnetosome surface or inserted into the membrane during magnetosome maturation (12,31). The complex magnetosome formation process is considered to require the spatial regulation of magnetosome proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the formation of magnetosomes confers a magnetic moment to the cells and allows them to migrate along oxygen gradients in an aquatic environment under the influence of the Earth's geomagnetic field (7). Based on recent molecular analyses in Magnetospirillum magneticum AMB-1 and Magnetospirillum gryphiswaldense MSR-1, Ͼ30 proteins (magnetosome proteins) have been suggested to be involved in the process of magnetosome formation (11)(12)(13). Moreover, the genes encoding magnetosome proteins are conserved in the genomes of magnetotactic bacteria and appear in the form of a genomic island-like structure (11,12,14) that is specifically referred to as the magnetosome island (MAI).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In MSR, deletion of the entire mamXY operon that encodes various functions in redox and transport of iron also caused a mixed phenotype, characterized by smaller, regular-shaped magnetite crystals that were flanked by irregular-shaped tiny flake-like hematite crystals. Unlike deletions of all other magnetosome genes, which consistently resulted in crystal size reductions of various degrees, the loss of mms36 and mms48 (within the mms6 operon) intriguingly caused the synthesis of fewer but larger magnetite crystals (18). Plasmid expression of the entire mamGFDC operon in the wild type (WT) also resulted in the formation of slightly enlarged (by 14.7%) magnetite particles (2).…”
mentioning
confidence: 99%
“…In the native host MSR, the large mamAB operon alone is sufficient to sustain rudimentary magnetite biomineralization in the absence of all other magnetosome genes (16). From the 17 mamAB operon genes, a subset of only a few (mamE, mamM, mamO, mamQ, and mamB) is essential for magnetite biomineralization, while in single-deletion mutants of the other genes, biomineralization was impaired to different degrees (18). The smaller mamGFDC, mms6, and mamXY operons are not essential but have accessory roles in controlling the biomineralization of properly sized and shaped crystals (2,16,19).…”
mentioning
confidence: 99%